(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The main objective of this research work was to determine the percentage of germination of microorganisms translocated from the large intestine to the internal organs. The percentage of microorganisms that passed through the large intestine from the peripheral blood of irradiated laboratory animals increased as the observation period increased. Analysis of the results showed that irradiation increases the permeability of the colon mucosa against the background of general immunodeficiency. In prophylactically biocorrected, irradiated animals, the percentage of germination of microorganisms decreased over time. In both groups, its values were significantly higher than in the control group. The aim of the study was to experimentally study the degree of occurrence of microorganisms that provide the phenomenon of bacterial translocation in the dynamics of observation under the influence of acute irradiation.